Comparison of short-term outcomes between single incision laparoscopic cholecystectomy and conventional 4-port laparoscopic cholecystectomy - ., Vishwanath; Palaniappan, Rajkumar; Premkumar, Balachandran (International Surgery Journal, 2019)
Background: Various numbers of case series, studies and randomized control trials conducted for comparison of Single port and Multi port cholecystectomy, however the benefit of Single Port cholecystectomy is still debatable. Methods: A prospective non-randomized comparative study was done to compare short term outcomes between SILS Cholecystectomy and Conventional 4-port Laparoscopic Cholecystectomy. Total of 85 patients underwent surgery out of which 5 cases were excluded (4 due to loss of follow up and 1 due conversion from SILS to LAP). There were 40 cases in each group, two group named as LAP (conventional 4-port laparoscopic cholecystectomy) group and SILS (single incision laparoscopic cholecystectomy) group. Results: On comparison of pain scores at 6 hours and 12 hours postoperatively and at the time of discharge between two groups there was significant difference at 12 hours postoperatively and at the time of discharge. The mean operative time in SILS group was similar to that of LAP group. The cosmesis score ranges from 2 to 10(1-5 for each questions) with 2 being best and 10 being worst appearance of scar. In LAP group, the mean cosmesis score was 4.65±0.9(SD) whereas, in SILS group it was 2.25±0.43(SD). On comparison between two groups there was significant difference (p= 0.0001). The quality of life total score on comparison between two groups there was significant difference in quality of life score (P=0.0001). Conclusions: It is concluded that SILS cholecystectomy is better than LAP and it should be preferred.